Acoustic wave velocity in Ag/Fe nanolayers - Aleksiejuk, Mikołaj; Rejmund, Feliks (Archives of Acoustics, 2007)
The paper presents the results of acoustic wave velocity investigation in metallic Ag/Fenanolayers deposited on GaAs substrate. Measurements of velocity were performed usingfemtosecond technique. Ag/Fe samples were characterized by different thickness of bilayers.On the basis of experimental results of velocities, effective elastic constants $c_{11}$ were evaluated.In the range of bilayers thickness above 80 Å the $c_{11}$ values are in accordance withthose calculated from the elastic constants of bulk materials (Rytov model). For lower valuesof bilayer thickness elastic constants exhibit large decrease. Grimsditch’s model was appliedto interpret changes of elastic constants dependence for low bilayer thickness. This modelcontains an additional interlayer treated as the parameter. Comparison the values of theoreticalelastic constants obtained by applying of Grimsditch model with those calculated fromexperiment shows qualitative accordance in the range of small bilayer thickness.